Penerapan Prinsip Good Governance Dalam Pelayanan Publik Di Kantor Desa Modayag Kecamatan Modayag Kabupaten Bolaang Mongondow Timur - Meisy Sangari; FEMMY TULUSAN; RULLY MAMBO (JURNAL ADMINISTRASI PUBLIK, 2023)
Abstract This research is to find out how the principles of good governance are implemented in public services at the Modayag Village Office, Modayag District, East Bolaang Mongondow Regency? This research aims to determine the application of good governance principles in public services at the Modayag Village Office, Modayag District, East Bolaang Mongondow Regency. This research is qualitative research with a descriptive approach. The informants in this research were the Modayag Village Secretary, the Head of Modayag Village Planning Affairs, Modayag Village Office Employees, Modayag Village Community. Data analysis in this research uses data reduction, data presentation, and drawing conclusions. The results of the research show the implementation of good governance in public services at the Modayag Village Office, namely: (1) Transparency, the Modayag Village Government has not been optimal in conveying information related to the services provided, as evidenced by the absence of service information as well as procedures and conditions for obtaining services on information boards, (2) Accountability, the Modayag Village Government has not implemented well the presentation of information on the implementation of activities and there is no physical evidence regarding accountability reports, (3) Responsiveness, the Modayag Village Government has been very good at welcoming the community, but still lack of speed and punctuality in service, this is proven by employees who lack discipline when carrying out their duties, are not in the office during working hours and lack of understanding of the types of services available which hinders serving community needs, (4) Effectifitas and Effeciency, the Modayag Village Government has not implemented it properly , this is proven by employees who are unable to use existing facilities and infrastructure such as computers, so that administrative services such as correspondence have to wait for those who can use computers before they can be handled, what is more fatal is that service users are directed to the photo/copy place to ask for a letter to be made. required then return to the village office to ask for the number and signature.  Keywords:  Implemented Of Good Governance, Public Service.   Abstrak Penelitian ini untuk mengetahui bagaimana penerapan prinsip good governance dalam pelayanan publik di Kantor Desa Modayag Kecamatan Modayag Kabupaten Bolaang Mongondow Timur?. Penelitian ini bertujuan untuk dapat mengetahui penerapan prinsip good governance dalam pelayanan publik di Kantor Desa Modayag Kecamatan Modayag Kabupaten Bolaang Mongondow Timur. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif. Informan dalam penelitian ini adalah Sekretaris Desa Modayag, Kepala Urusan Perencanaan Desa Modayag, Pegawai Kantor Desa Modayag, Masyarakat Desa Modayag. Analisis data pada penelitian ini menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian menunjukan penerapan good governance dalam pelayanan publik di Kantor Desa Modayag yaitu : (1) Transparansi, Pemerintah Desa Modayag belum maksimal dalam menyampaikan informasi yang berkaitan dengan pelayanan yang diberikan, dibuktikan dengan tidak adanya informasi pelayanan serta prosedur dan syarat-syarat untuk mendapatkan pelayanan di papan informasi, (2) Akuntabilitas, Pemerintah Desa Modayag belum menerapkan dengan baik mengenai penyajian informasi penyelenggaraan kegiatan serta tidak adanya bukti fisik mengenai laporan pertanggungjawaban, (3) Daya Tangkap, Pemerintah Desa Modayag sudah sangat baik dalam menyambut masyarakat, akan tetapi masih kurang cepat dan tepat waktu dalam pelayanan, ini dibuktikan oleh pegawai yang kurang disiplin saat menjalankan tugas, saat jam kerja tidak berada di kantor dan kurang memahami tentang jenis pelayanan yang ada membuat pelayanan kebutuhan masyarakat terhambat, (4) Efektifitas dan Efisien, Pemerintah Desa Modayag belum menerapkan dengan baik, ini dibuktikan dengan pegawai yang kurang bisa menggunakan sarana dan prasarana yang ada seperti komputer, sehingga untuk pelayanan administrasi seperti surat-menyurat harus menunggu yang bisa menggunakan komputer baru bisa ditangani, yang lebih fatalnya pengguna layanan diarahkan ke tempat foto/copy untuk minta dibuatkan surat yang diperlukan lalu balik ke kantor desa untuk meminta nomor dan tanda tangan.  Kata Kunci: Penerapan Good Governance, Pelayanan Publik.